(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on the scientific production regarding the variable Policies for Educational Inclusion during the period 2016-2020, by identifying research papers published in high impact journals indexed in Scopus database, in order to describe the main characteristics on the volume of publications. Similarly, a qualitative analysis of some publications was applied to identify the position of different authors regarding the Policies for Educational Inclusion. As a result, a total of 1783 publications were obtained at a global level during the above-mentioned period, after identification by means of a series of parameters established for the search. Among the findings is that the United States was the country with the highest number of publications during the period 2016-2020 regarding the variable of study, which recorded a total of 343 documents in total. The year where the highest number of publications were registered in Scopus was 2020 when a total of 486 research papers were reported. Of the total number of publications made during the mentioned period, 1375 were made through theories framed in the Social Sciences, and the type of publication that was most frequently used by the authors was the Scientific Article which represents 74.6% of the total production, that is 1331 documents.